Re: A New Risk-Scoring System for Colorectal Cancer and Polyp Screening - Levent Erdem; Erdem Koçak (Turkish Journal of Gastroenterology, 2022)
Cite this article as: Erdem L, Koçak E. Re: A new risk-scoring system for colorectal cancer and polyp screening. Turk J Gastroenterol. 2022;33(12):1080.